Tunable Chemical Reactivity and Selectivity of WO3/TiO2 Heterojunction for Gas Sensing Applications. Issue 12 (12th December 2022) - Galstyan, Vardan; Poli, Nicola; Golovanov, Viacheslav; D'Arco, Annalisa; Macis, Salvatore; Lupi, Stefano; Bolli, Eleonora; Kaciulis, Saulius; Mezzi, Alessio; Comini, Elisabetta
Abstract: Nowadays, there is a dramatically growing demand for nanocomposite materials with new functionalities for their application in chemical gas sensors and other catalytic devices. Moreover, green synthesis methods are intensively employed in the preparation of semiconductor nanostructures to reduce the hazardous effects on human health and the environment. Here the fabrication of a nanocomposite material based on WO3 and TiO2 (WO3 /TiO2 ) with unusual electronic band alignment and novel gas sensing properties is reported. The material is synthesized by an eco‐friendly process based on the water vapor‐induced oxidation of tungsten/titanium metallic films. The pristine WO3 is highly sensitive to acetone, where the response of the material is enhanced by its operating temperature. Instead, WO3 /TiO2 composite shows principally different sensing performance and it has a good selective response to carbon monoxide at a relatively low operating temperature. The obtained results indicate that the significant differences between the functionalities of pristine WO3 and WO3 /TiO2 material can be attributed to the band alignment and the direction of charge transfer in the WO3 /TiO2 heterojunction. Hence, an efficient way for the development of WO3 /TiO2 nanocomposites, which can be useful for the engineering and optimization of gas sensing and catalytic properties of WO3, is presented. Abstract : Synthesis of WO3 /TiO2 heterojunction with an unusual electronic band alignment, where the valence band maximum of WO3 is higher than the valence band maximum of TiO2 . Herein, the sensing performance of the WO3 acetone sensor is modified and the WO3 /TiO2 heterojunction has a very selective response to carbon monoxide at a relatively low operating temperature.